Evidence of new pathogenic Theileria species in dogs - Dixit, Pooja (Springer-Verlag, 2010)
Babesiosis, caused by tick-borne haematozoan organisms of the genus Babesia, is a parasitic disease of domestic and wild mammals. Canine Babesidae have historically been classified as “large Babesia” (Babesia canis) and “small Babesia” (Babesia gibsoni) based on the size of their intraerythrocytic forms. Recent publications, however, suggest that the diversity of piroplasm species infecting dogs might be greater than previously appreciated. Sequencing and phylogenetic analysis of the ssrRNA gene has revealed that canine piroplasms are found in three clades, ‘true’ Babesia sp. (B. canis and B. gibsoni), Theileria annae and Theileria-like group (B. conradae). This newly recognised piroplasm T. annae appears to be hyperendemic in northwest Spain. The vector for this emergent canine infection remains undescribed, although the Ixodeshexagonus is suspected based on their presence upon the dogs in NW Spain and the relative absence of others. These observations have introduced a major change in the approach to the epidemiology of babesiosis in dogs. More clinical samples and data will need to be collected and analyzed to understand the importance of Theileria species in dogs.